31.7k views
16 votes
Y=3x-7y=3x−7 Complete the missing value in the solution to the equation. (1,_) PLEASE QUICK

User Colorlace
by
7.7k points

2 Answers

11 votes

Answer:-4

Step-by-step explanation:bc khan

User Dhpratik
by
6.7k points
11 votes

Answer:

-4

Explanation:

The two equations you have are:

y = 3x - 7

x = 1 (this comes from the x value being 1)

To solve for y, use the substitution property of equality to replace x in the equation:

where x = 1,

y = 3(1) - 7

y = -4

User Dmila Ram
by
7.6k points